2022
DOI: 10.1192/bjo.2022.549
|View full text |Cite
|
Sign up to set email alerts
|

Differences in associations between family functioning and anxious and depressive symptoms in Chinese women and their partners in early pregnancy

Abstract: Background Family functioning is associated with anxiety and depression. Perinatal depression and anxiety are common and influence the well-being of women, partners and their offspring. However, little is known about differences in associations between family functioning and mood symptoms in women and their partners in early pregnancy. Aims Investigating differences in associations between family functioning and anxious and depressive symptoms in women and their partners in early pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
1
2
Order By: Relevance
“…Unlike previous studies that found a correlation between family health and anxiety/depression (Dang et al., 2021; Qin et al., 2022). Our results showed that the association was not significant.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Unlike previous studies that found a correlation between family health and anxiety/depression (Dang et al., 2021; Qin et al., 2022). Our results showed that the association was not significant.…”
Section: Discussioncontrasting
confidence: 73%
“…Unlike previous studies that found a correlation between family health and anxiety/depression (Dang et al, 2021;Qin et al, 2022).…”
Section: The Associations Between Family Health and The Pain/discomfo...contrasting
confidence: 72%
“…Besides, family functioning also plays a vital role in the health of family members during pregnancy. On the one hand, impaired family functioning would increase the likelihood of symptoms of depression and anxiety in pregnant females and their partners during early pregnancy ( Qin et al, 2022 ). On the other hand, maternal exposure to poor family functioning during pregnancy would influence the offspring’s brain development in the hippocampus ( Xerxa et al, 2021 ) and increase their vulnerability to being victimized by peers in the future ( Lereya and Wolke, 2013 ).…”
Section: Introductionmentioning
confidence: 99%